1997
DOI: 10.1136/thx.52.4.369
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and prostacyclin as test agents of vasoreactivity in severe precapillary pulmonary hypertension: predictive ability and consequences on haemodynamics and gas exchange

Abstract: Abstractmay make it a more appropriate agent for testing the vasodilator response. Background -In patients with primary (Thorax 1997;52:369-372) pulmonary hypertension who respond to vasodilators acutely, survival can be im- Keywords: pulmonary hypertension, vasodilators, nitric proved by the long term use of calcium oxide, prostacyclin, calcium channel blockers. channel blockers. However, testing for such a response with calcium channel blockers or prostacyclin (PGI 2 ) may causeIn patients with primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 17 publications
0
21
0
4
Order By: Relevance
“…Pharmacological challenge with inhalative NO, a short-acting vasodilatory agent possessing selectivity for the pulmonary circulation, is now largely accepted as a convenient tool to detect patients with a good acute responsiveness to vasodilators [5,19]. It has previously been shown that haemodynamic responsiveness to inhaled NO is a good predictor for a beneficial response to high-dose oral calcium channel blockers [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological challenge with inhalative NO, a short-acting vasodilatory agent possessing selectivity for the pulmonary circulation, is now largely accepted as a convenient tool to detect patients with a good acute responsiveness to vasodilators [5,19]. It has previously been shown that haemodynamic responsiveness to inhaled NO is a good predictor for a beneficial response to high-dose oral calcium channel blockers [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, such pharmacological therapy may be hazardous in haemodynamic "nonresponders" [4] and is therefore discouraged. Instead of directly testing with calcium channel blockers during right heart catheterization, vasoreactivity testing with inhaled nitric oxide (NO), being advantageous due its very short half-life and its selectivity for the pulmonary vasculature, is a widely-accepted procedure for detecting patients who are eligible for high-dose calcium channel blocker therapy [4][5][6].…”
mentioning
confidence: 99%
“…10 hastanın yer aldığı ve eski PVT test kriterlerinin kullanıldı-ğı bir çalışmada ise nifedipin, iNO ve epoprostenol ile uygulanan teste tüm hastaların %60'ı yanıt vermiş ancak iNO'ya göre nifedipin ve epoprostenol daha fazla yan etkiye neden olmuştur (PaO2, kan basıncı ve SVD'de düşme) (46). iNO'ya karşı adenozin Brezilya'dan yapılan yeni bir çalışmada Oliveira ve ark.…”
Section: Epoprostenolunclassified
“…This was carried out while patients breathed room air, after oxygen therapy at 100% for 15 minutes and use of nitric oxide in an initial concentration of 10 ppm; in the absence of response, the concentration was increased every 10 minutes, up to 80 ppm. 6 Oral nifedipine was initially given in the dose of 5 mg to patients weighing more than 30 kg and in the dose of 0.2 mg/kg to children, with a 50% increase in the dose every 6 hours in case of no response or of side effects. Pulmonary reactivity tests were defined as positive in the presence of a decrease greater than 20% in mean PP, without reduction of systemic output and with maintenance of the reduction in the pulmonary systolic pressure (PSP)/systolic arterial pressure (SAP) ratio greater than 20%.…”
Section: Methodsmentioning
confidence: 99%
“…It is common knowledge that most patients do not respond to calcium antagonists and may have severe side effects, which shows the importance to perform acute reactivity tests in order to select those patients who would definitely benefit from their use. Pulmonary reactivity tests employ oxygen at 100% and short half-life drugs with pulmonary vasodilatory action, such as adenosine, 5 prostacyclin, 6 acetylcholine and mainly nitric oxide, 7 since it is a selective and short-acting pulmonary vasodilator.…”
Section: Introductionmentioning
confidence: 99%